2021
DOI: 10.1038/s41598-021-85658-9
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic cave carbonate and implications for thawing permafrost at Winter Wonderland Cave, Utah, USA

Abstract: Winter Wonderland Cave contains perennial ice associated with two types of cryogenic cave carbonate (CCC) formed during the freezing of water. CCCfine is characterized by relatively high δ13C values, whereas CCCcoarse exhibits notably low δ18O values indicating precipitation under (semi)closed-system conditions in a pool of residual water beneath an ice lid. Previous work has concluded that CCCcoarse forms during permafrost thaw, making the presence of this precipitate a valuable indicator of past cryospheric … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…the "CCC window", Spötl et al, 2021;Koltai et al, 2021), indicating that the cave was surrounded by permafrost at the time of CCC formation. A study of Winter Wonderland Cave, USA (Munroe et al, 2021), validated this genetic model by observing very recent formation of CCCs in the exact setting proposed by Žák et al (2004).…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…the "CCC window", Spötl et al, 2021;Koltai et al, 2021), indicating that the cave was surrounded by permafrost at the time of CCC formation. A study of Winter Wonderland Cave, USA (Munroe et al, 2021), validated this genetic model by observing very recent formation of CCCs in the exact setting proposed by Žák et al (2004).…”
Section: Introductionmentioning
confidence: 66%
“…A possible explanation for this high variability can be entertained by con-sidering the dynamic nature of CCC-forming pools. Munroe et al (2021) reported that the residual pools holding CCCs in Winter Wonderland Cave show different degrees of discolouration of the residual water, indicating that progressive freezing altered the physio-chemical properties of the residual water. One possible explanation could be that the ratio between the different Th sources listed above changes, thereby altering the Th isotopic composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have defined the CCC formation window between -1 and 0 °C, whereas a temperature between -0.5 and 0 °C is deemed more likely (Koltai et al, 2021;Spötl et al, 2021). Recent studies reported in-situ finds of CCCs and provided further support for this genetic model of slowly freezing ionized water at temperatures slightly below 0 °C , which previously had relied on indirect field evidence and the carbon and oxygen isotopic composition (Bartolomé et al, 2015;Munroe et al, 2021). CCC formation https://doi.org/10.5194/cp-2023-72 Preprint.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, temporal and spatial changes in past permafrost distribution have been identified using speleothems (stalagmites, flowstones) in circumpolar and polar regions (e.g., Vaks et al, 2013Vaks et al, , 2020Moseley et al, 2021) as well as in mid-latitude regions (e.g., Lundberg and McFarlane, 2007;Fankhauser et al, 2016;Lechleitner et al, 2020). Recently, coarse cryogenic cave carbonates (CCCcoarse), that form during slow freezing of water inside caves, have been used as indicator of permafrost degradation, permafrost thickness, and subsurface ice formation (Žák et al, 2004Richter et al, 2010;Luetscher et al, 2013;Orvošová et al, 2014;Spötl and Cheng, 2014;Bartolomé et al, 2015;Dublyansky et al, 2018;Koltai et al, 2020;Munroe et al, 2021).…”
Section: Introductionmentioning
confidence: 99%